(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. A red eye includes various etiology diseases of the ocular surface (eyelids, conjunctiva, and cornea) as well as of the vascular tract and lacrimal apparatus, the main feature of which is hyperemia of the conjunctiva of the eye. The purpose of the present study was to study the efficacy of antibacterial fusidic acid drug in patients with the red eye. Material and Methods. We observed 60 patients (120 eyes) with the red eye. In case that conjunctival flora was sensitive to Futaron, the patients were prescribed the drug instillations 4 times a day for 7 days followed by repeated microbiological control. Efficacy of Futaron was determined due to terms and occurrence of pathogen eradication according to data of microbiological test of the conjunctival discharge. Results. When performing the microbiology test of the conjunctival discharge, Staphylococcus epidermidis was noted in 31 patients (51.6%). Of them, after Futaron instillations, reseeding was pure in 23 patients, and staphylococcus growth continued in 8 patients (25.6%). In all twelve patients (20%) with Moraxella determined, agent eradication was achieved against the background of Futaron instillations. Streptococcus haemolyticus was detected in the culture from the conjunctiva in seven patients (11.7%). Herewith, reseeding was pure in four patients (57.2%) and staphylococcus persistence was noted in three of them (42.8%). Futaron instillations for 7 days facilitated pathogenic flora eradication in four patients (6.7%) with Escherichia coli defined and in three patients (5%) with Staphylococcus aureus. Conclusions. Futaron eye drops is an effective and safe drug for treatment of red eye patients and they are most effective when Staphylococcus epidermidis and Moraxella are defined in the culture from the conjunctiva.